ID: 81. Issue 1 (November 2015) - Faget, Julien; Contat, Caroline; Zangger, Nadine; Ramay, Hena; Peters, Solange; Meylan, Etienne
<x xml:space="preserve">Abstract</x> With over 1.5 million deaths yearly, lung cancer has become the leading cause of cancer-related mortality worldwide. Although targeted therapies are emerging to combat non-small cell lung cancer (NSCLC), the principal type of lung cancer, they are currently limited to a small fraction of tumors with defined oncogenic alterations, and no specific treatment exists against tumors carrying activating mutations in the most frequently mutated proto-oncogene, KRAS. Here we show an association between expression of the osteoclast differentiation factor, receptor activator of NF-kappaB (RANK) ligand (RANKL) and overall survival in NSCLC, and an impaired progression of Kras-mutant tumors upon pharmacological blockade of RANKL in several genetically-engineered mouse models of NSCLC. RANKL blockade used as monotherapy led to a rapidly diminished tumor growth rate, with shrinkage in a large proportion of tumors, as monitored by in vivo micro-computed tomography. The anti-tumor response, which was characterized by apoptosis induction and NF-kappaB pathway attenuation in tumor cells, as well as increased dendritic cell maturation with proliferation of CD8+ T cells in the tumor microenvironment, lasted for a prolonged period of time without noticeable resistance. Combined administration of the standard chemotherapy cisplatin with the RANKL inhibitor to mirror an ongoing clinical trial revealed increased efficacy compared to each treatment alone. Finally, we report the case of a patient whose primary lung tumor responded to a RANKL inhibitory drug. Altogether, our results indicate that RANKL blocking agents used as monotherapies or in combination treatment impair the growth of primary lung tumors.